Pengaruh Pemahaman Kode Etik Akuntan dan Religiusitas terhadap Perilaku Etis Mahasiswa Akuntansi - Fouri Ayu Ardani; Fefri Indra Arza (Universitas Negeri Padang, 2023)
The problem of professional ethics in accounting has become the center of public attention so that all professions are required to work professionally. This study aims to analyze the effect of understanding the accountant's code of ethics and religiosity on the ethical behavior of accounting students. This research is a causative research using a quantitative approach. The data used in this study is primary data with data collection techniques using questionnaires. The population in this study were students majoring in accounting for the 2018/2019 academic year, Faculty of Economics, Padang State University. The sample technique used in this research is purposive sampling. The number of samples in this study were 146 students from 231 accounting students at Padang State University. The hypothesis in this study was tested using multiple linear regression analysis with IBM SPSS 22. The results of this study (1) understanding of the accountant's code of ethics has a significant positive effect on ethical behavior of accounting students at Padang State University and (2) religiosity has no effect on ethical behavior of university accounting students Padang Country.